The Oxford handbook of the Bible and the Reformation - McNutt, Jennifer Powell (Oxford University Press, 2024)
This volume explores the biblical canon, translation and print, the development of Reformation hermeneutics, the history of Bible commentators, and exegesis relating to key texts and theological themes of Reformation writing and discourse